The Co-Prime Probability of p-Groups / Norarida Abdul Rhani ...[et al.] - Abd Rhani, Norarida; Mohd Ali, Nor Muhainiah; Sarmin, Nor Haniza; Erfanian, Ahmad (Unit Penerbitan UiTM Kelantan, 2019)
The commutativity degree of Gcanbe used to measure how close a group is to be abelian. This concept has been extended to the probability that two random integers are co-prime. Two integers s and tare said to be co-prime if their greatest common divisor is equal to one. This concept hasbeen further extended to the co-prime probability of G, where the probability of the order of a random pair of elements in the group are co-prime.In this paper, the co-prime probability for all p-groups, where pis prime number isdetermined